2014
DOI: 10.1186/1471-2229-14-133
|View full text |Cite
|
Sign up to set email alerts
|

A rice calcium-dependent protein kinase OsCPK9 positively regulates drought stress tolerance and spikelet fertility

Abstract: BackgroundIn plants, calcium-dependent protein kinases (CDPKs) are involved in tolerance to abiotic stresses and in plant seed development. However, the functions of only a few rice CDPKs have been clarified. At present, it is unclear whether CDPKs also play a role in regulating spikelet fertility.ResultsWe cloned and characterized the rice CDPK gene, OsCPK9. OsCPK9 transcription was induced by abscisic acid (ABA), PEG6000, and NaCl treatments. The results of OsCPK9 overexpression (OsCPK9-OX) and OsCPK9 RNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 69 publications
(87 reference statements)
4
137
0
Order By: Relevance
“…In addition, the expression data used in this study also show some discrepancies with other published studies. For example in rice, OsCPK9 and OsCPK21 have been reported to be induced by salt stress and ABA 22, 48, which is not observed in Fig. 4F.…”
Section: Resultsmentioning
confidence: 78%
“…In addition, the expression data used in this study also show some discrepancies with other published studies. For example in rice, OsCPK9 and OsCPK21 have been reported to be induced by salt stress and ABA 22, 48, which is not observed in Fig. 4F.…”
Section: Resultsmentioning
confidence: 78%
“…(Wei et al, 2014). Taken together these results suggest that the genes in this cluster contribute to drought tolerance by regulating osmotic adjustment and ROS scavenging processes and can also be putative candidates for increasing yield under drought.…”
Section: Examples Of Drought Transcriptional Modulesmentioning
confidence: 65%
“…However, the abundance of CDPKs increased in the drought-tolerant genotype of Z. mays [41]. It has been reported that overexpression of the CDPK gene can enhance drought tolerance in transgenic Arabidopsis [79,80] and O. sativa [81]. These reports imply the important role of CDPKs in plant stress tolerance.…”
Section: Drought Sensing and Signalingmentioning
confidence: 99%